Strengthening Continuity Coaching Goals (Sustainable Development Goals) through the Facility Development Plan and Poetry Image Extension to Elementary School Students in Dolok Ilir I (Bah Bolon) Dolok Batu Nanggar District, Simalungun Regency - Dardanila; Susilo, Hariadi; Mulyadi; Widayati, Dwi; Tafsin, Ma’ruf; Ariani, Farida (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Simalungun Assisted Village Team conducted a preliminary survey based on secondary and primary data. The survey is primarily carried out through direct observation and in-depth discussions with stakeholders such as village heads and other elements of village leadership. The result of the discussion is the problem of wall fence facilities and understanding the image of poetry for students. The solution is to improve sustainable development goals. The USU Assisted Village Team carried out activity methods in the form of building wall fences and providing counseling to elementary school students about understanding the image of poetry, namely. (1) Vision Imagery; (2) Auditory Imagery; (3) Motion Imagery; (4) Tactile Imagery; (5) Olfactory Imagery; (6) Tasting Imagery; (7) Image of Feeling. Furthermore, it is hoped that several activity outcomes will be achieved, namely, (1) Being able to encourage the growth of community initiative and creativity to overcome problems through improving facilities and counseling on the understanding of poetry image (2) Produce scientific publications and publications to the public on Sustainable Development Goals (SDGS) through the Assisted Village in Dolok Ilir I Village, Dolok Batu Nanggar District, Simalungun Regency.